Uji Efektivitas Ekstrak Etanol Daun Labu Siam (Sechium edule (Jacq.) Swartz) Sebagai Penyembuh Luka Sayat pada Tikus Putih (Rattus norvegicus) - Charly J. Watung; Christel N. Sambou; Jabes W. Kanter; Reky R. Palandi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Herbal plants refer to plant species that can be used as medicinal herbs, either individually or in combinations, believed to prevent and facilitate wound healing. One such herbal plant commonly used by the community is the leaves of Chayote (Sechium edule (Jacq.) Swartz), believed to accelerate the healing of wounds. This research aims to determine the effectiveness of ethanol extract from Chayote leaves (Sechium edule (Jacq.) Swartz) in healing incision wounds in white rats (Rattus norvegicus). The samples used were 15 male rats. A 1 cm incision wound was made on the rats' backs using a surgical blade. The research employed a Completely Randomized Design (CRD) with 5 treatments: negative control, positive control (10% povidone iodine), and 3 concentrated extracts (5%, 10%, 15%) with 3 repetitions each. The treatments were administered twice a day for seven days. The calculation of wound healing percentage in rats based on the research results indicated that Chayote leaf extract with a concentration of 15% showed 100% effectiveness in healing incision wounds in white rats.